2009
DOI: 10.4174/jkss.2009.76.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy in Children with Perforated Appendicitis

Abstract: Purpose:It is controversial to do laparoscopic appendectomy in children with perforated appendicitis. Recently, we have adopted laparoscopic appendectomy as a first-choice method in children with perforated appendicitis. Results: The operation times were significantly longer for the LA group than for the OA group (OA group 76.3±23.7 vs. LA group 95.4±32.4 min) (P<0.05). The hospital days were also longer in the LA group than the OA group (OA group 8.7±4.4 vs. LA group 11.0±6.3 (days)). However, there was no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This instability of electron beam is undesirable because it limits not only the spectral purity of the electromagnetic field but also the efficiency of the conversion of the electron energy into electromagnetic energy. It has been shown that the use of tapered wigglers offer a way to avoid these problems and the efficiency can be considerably increased by optimizing the tapering [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This instability of electron beam is undesirable because it limits not only the spectral purity of the electromagnetic field but also the efficiency of the conversion of the electron energy into electromagnetic energy. It has been shown that the use of tapered wigglers offer a way to avoid these problems and the efficiency can be considerably increased by optimizing the tapering [7][8][9].…”
Section: Introductionmentioning
confidence: 99%